2017
DOI: 10.3389/fimmu.2017.00821
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Interleukin-6 Promotes Allogeneic Bone Marrow Engraftment and Prolonged Graft Survival in an Irradiation-Free Murine Transplant Model

Abstract: Transfer of recipient regulatory T cells (Tregs) induces mixed chimerism and tolerance in an irradiation-free bone marrow (BM) transplantation (BMT) model involving short-course co-stimulation blockade and mTOR inhibition. Boosting endogenous Tregs pharmacologically in vivo would be an attractive alternative avoiding the current limitations of performing adoptive cell therapy in the routine clinical setting. Interleukin-6 (IL-6) potently inhibits Treg differentiation and its blockade was shown to increase Treg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 68 publications
3
16
0
Order By: Relevance
“…In this respect, it is of interest that IL-6 blockade accentuated Treg expansion by IL-2 cplx and thereby may function by prolonging Treg function. This notion is in line with reports that IL-6 blockade in mice can stabilize Treg function (41) and also led to an increase in Treg numbers (20), both for thymic-derived and peripherally induced Tregs, and thereby reduces the severity of GVHD (42). Whether IL-6 blockade has similar effects on human Tregs is still unclear (43), although recent data have shown that anti-IL-6R mab (tocilizumab) therapy is beneficial for renal transplantation (44).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this respect, it is of interest that IL-6 blockade accentuated Treg expansion by IL-2 cplx and thereby may function by prolonging Treg function. This notion is in line with reports that IL-6 blockade in mice can stabilize Treg function (41) and also led to an increase in Treg numbers (20), both for thymic-derived and peripherally induced Tregs, and thereby reduces the severity of GVHD (42). Whether IL-6 blockade has similar effects on human Tregs is still unclear (43), although recent data have shown that anti-IL-6R mab (tocilizumab) therapy is beneficial for renal transplantation (44).…”
Section: Discussionsupporting
confidence: 91%
“…Since previous studies used only brief (3 d) treatment with IL-2 cplx, it was important to examine the effects of prolonged IL-2 cplx treatment. We also examined whether graft survival could be improved by IL-6 blockade (20,21). In this respect, histologic rejection of allografts is known to be associated with IL-6 expression, both in experimental models (22) and patients (23,24), and injection of anti-IL-6 mab can delay graft rejection (25).…”
Section: Significancementioning
confidence: 99%
“…This plasticity in the secretory potential of MSCs represents limitations when cultured MSCs producing TGF-β are transferred into the inflammatory environment of the diseased retina. To prevent activation of pro-inflammatory cells, MSCs could be co-administrated with antibody anti-IL-6 or anti-IL-6 receptor, as this has been tested in patients with kidney allografts[76,77]. It has been shown that blocking of the IL-6 pathway can attenuate inflammation, support the activation of Tregs and enhance allograft survival.…”
Section: Resultsmentioning
confidence: 99%
“…Coadministration of Tocilizumab to standard GvHD prophylaxis revealed promising potential in a phase I/II trial ( 32 ) and is also tested in several transplant trials ( 103 ). In the experimental setting, blocking IL-6 displayed a beneficial effect on the induction of chimerism and tolerance in non-human primates and mice ( 104 , 105 ).…”
Section: Future Prospectsmentioning
confidence: 99%